1987
DOI: 10.1111/j.1365-2141.1987.tb01309.x
|View full text |Cite
|
Sign up to set email alerts
|

Cianidanol and its metabolites bind tightly to red cells and are responsible for the production of auto‐ and/or drug‐dependent antibodies against these cells

Abstract: Cianidanol ((+)-2-(3,4-dihydroxyphenyl)-3, 5, 7-chromantriol) is a flavonoid which has been associated with severe immune haemolysis by as yet unclear mechanisms. We report six patients who developed haemolysis while receiving the drug. The disorder was episodic in all patients and resolved after discontinuing the drug. The causative antibodies could be demonstrated in all six cases, even when the haemolytic episode was more than 1 year prior to this study. One patient had developed drug-independent IgG autoan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…The results herein presented are similar to those re ported by Salama and Mueller-Eckhardt [8] and Casaril et al [12] in patients with cyanidanol-induced immune he molysis. The IgG autoantibodies could not be distin guished serologically from those observed in warm au toimmune hemolytic anemia; the hematological findings were also normal after suspending cyanidanol.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The results herein presented are similar to those re ported by Salama and Mueller-Eckhardt [8] and Casaril et al [12] in patients with cyanidanol-induced immune he molysis. The IgG autoantibodies could not be distin guished serologically from those observed in warm au toimmune hemolytic anemia; the hematological findings were also normal after suspending cyanidanol.…”
Section: Discussionsupporting
confidence: 81%
“…Several authors have demonstrated the pres ence of drug-dependent antibodies against red blood cells [4][5][6][7][8], In particular, Salama and Mueller-Eckhardt [8] showed that cyanidanol strongly combines with erythro cyte membranes, thus inducing the development of drugdependent antibodies and autoantibodies.…”
Section: Introductionmentioning
confidence: 99%
“…However, all rat blood samples exhibited very high, potentially lethal potassium levels (Table 5). Ciandanol and its metabolites, (+)-catechin-related compounds, have been implicated in at least six cases of hemolysis in humans (Salama and Mueller-Eckhardt 1987). In vitro hemolysis, however, can also occur in a blood sample owing to prolonged storage or storage in incorrect conditions (Cox 1981).…”
Section: Discussionmentioning
confidence: 99%
“…1 Sometimes the causative drugs appear to bind strongly to RBCs, for example, cianidanol, diclofenac, cefotetan, and piperacillin, and can also lead to acute and intravascular hemolysis. [1][2][3] During the acute phase of hemolysis, the DAT is not only positive for C3d, but also for IgG or, less frequently, IgM antibodies. These antibodies, unlike those in autoimmune hemolytic anemia (AIHA) of warm type, do not solely react with RBCs, but in combination with the drug.…”
mentioning
confidence: 99%